Fabrication of Ag nanostructures by the systematic control of annealing temperature and duration on GaN (0001) via the solid state dewetting. Issue 3 (30th November 2016) - Pandey, Puran; Kunwar, Sundar; Sui, Mao; Li, Ming‐Yu; Zhang, Quanzhen; Lee, Jihoon
Abstract : The gradual evolution of Ag nanostructures in terms of the configuration, size, and density of via the solid state dewetting is demonstrated on GaN (0001) by the systematic control of annealing temperature and duration with various Ag film thickness. Upon the annealing between 150 and 700 °C with the 20 nm Ag film, the hillocks, voids, irregular, and round dome shaped Ag nanoparticles (NPs) are fabricated based on various growth mechanisms: i.e., thermal diffusion and sublimation as well as the surface energy minimization. On the other hand, along with the systematic control of annealing duration between 0 and 3600 s with 10 nm Ag film 700 °C, the Ag NPs show gradually decreased size and density based on the concurrent influence of the Ostwald's ripening and sublimation of Ag atoms. The Raman, photoluminescence, and reflectance spectroscopy of the resulting Ag NPs are characterized in accordance with the various morphology evolution of Ag nanostructures.